Immunomodulatory and antioxidant effects of Glycyrrhiza uralensis polysaccharide in Lohmann Brown chickens - Zhou, Hui; Dai, Chen; Cui, Xuejie; Zhang, Tao; Che, Yanyun; Duan, Kun; Yi, Lei; Nguyen, Audrey D.; Li, Nannan; De Souza, Cristabelle; Wan, Xin; Wu, Yu; et al. (Frontiers in Veterinary Science, 2022)
Glycyrrhiza polysaccharide extract 1 (GPS-1) is a bioactive component isolated from Glycyrrhiza uralensis, also known as Chinese licorice. It appears to be pharmacologically active as an antibacterial, antiviral, and anti-tumor agent. GPS-1 has also been shown to buffer liver health and regulate the immune system. Moreover, GPS-1 is low cost and easy to extract. More study was needed to elucidate the biochemical pathways underlying the immunomodulatory and antioxidant benefits observed in Glycyrrhiza polysaccharide extract 1 (GPS-1). in vitro experiments on chicken lymphocytes and dendritic cells (DCs) show that GPS-1 significantly promotes the proliferation of immune cells and is linked to lymphocytes' secretion of IL-12, IFN-γ, and TNF-α by. DC secretion of NO, IL-2, IL-1β, IFN-γ, TNF-α, and IL-12p70 was also increased significantly. Additionally, GPS-1 also displayed a significant antioxidant effect in vitro, able to scavenge DPPH, hydrogen peroxide, ABTS, and other free radicals like superoxide anions. Separately, GPS-1 was tested in vivo in combination with the Newcastle disease virus (NDV) – attenuated vaccine. 120 Lohmann Brown chickens were vaccinated, while another 30 became the unvaccinated blank control (BC) group. For three consecutive days 1 mL of GPS-1 was administered at doses of 19.53 μg/mL, 9.77 μg/mL, or 4.88 μg/mL to the ND-vaccinated birds, except for the vaccine control (VC), where n = 30 per group. In vivo results show that GPS-1 combined with Newcastle disease (ND) vaccine had the best efficacy at significantly increasing chickens' body weight and ND serum antibody titer, enhancing their secretion of IL-2 and IFN- γ, and promoting the development of immune organs. The results also indicate that GPS-1 was able increase the proliferation of in vitro immune cells and elevate their cytokine secretion, which enhances the body's immune response. GPS-1 also clearly has the potential to be used as an immune adjuvant alongside ND vaccination.